Pathologic Function and Therapeutic Potential of Exosomes in Cardiovascular Disease - Ailawadi, Shaina (Biochim Biophys Acta, 2014)
The heart is a very complex conglomeration of organized interactions between various different cell types that all aid in facilitating myocardial function through contractility, sufficient perfusion, and cell-to-cell reception. In order to make sure all features of the heart work effectively, it is imperative to have a well-controlled communication system among the different types of cells. One of the most important ways the heart regulates itself is by the use of extracellular vesicles, more specifically, exosomes. Exosomes are types of nano-vesicles, naturally released from living cells. They are believed to play a critical role in intercellular communication through the means of certain mechanisms including direct cell-to-cell contact, long-range signals as well as electrical and extracellular chemical molecules. Exosomes contain many unique features like surface proteins/receptors, lipids, mRNAs, microRNAs, transcription factors and other proteins. Recent studies indicate that the exosomal contents are highly regulated by various stress and disease conditions, in turn reflective of the parent cell status. At present, exosomes are well appreciated to be involved in the process of tumor and infection disease. However, the research on cardiac exosomes is just emerging. In this review, we summarize recent findings on the pathologic effects of exosomes on cardiac remodeling under stress and disease conditions, including cardiac hypertrophy, peripartum cardiomyopathy, diabetic cardiomyopathy and sepsis-induced cardiovascular dysfunction. In addition, the cardio-protective effects of stress-preconditioned exosomes and stem cell-derived exosomes are also summarized. Finally, we discuss how to epigenetically reprogram exosome contents in host cells which makes them beneficial for the heart.